1988
DOI: 10.3109/02841868809090334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and Split-Course Radiotherapy as Primary Treatment in Carcinoma of the Larynx

Abstract: Based on our experience with conventional, daily irradiation, a split-course radiation schedule was introduced in 1978. The schedule, which was based on Cohen's models for squamous cell carcinoma and vascular damage respectively, predicted an improved tumour control and a reduced rate of late complications, e.g. late oedema, if the conventional, daily treatment was replaced by a split-course schedule. The schedule has later been abandoned, but the experience gained from split-course treatment at various dose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(53 citation statements)
references
References 15 publications
1
48
0
3
Order By: Relevance
“…An interim report from this trial has shown a better total survival compared to the earlier trial with split-course therapy, probably related to the change in treatment schedule (6). However, this trial is still on-going and no definite results can yet be reported.…”
Section: Discussionmentioning
confidence: 91%
“…An interim report from this trial has shown a better total survival compared to the earlier trial with split-course therapy, probably related to the change in treatment schedule (6). However, this trial is still on-going and no definite results can yet be reported.…”
Section: Discussionmentioning
confidence: 91%
“…However, when the break, is compensated by a lo'%, increase in total dose, split-course seems to be equally effective as continuous treatment (25). Overgaard et al (26) used a 20'% increase in the total dose but this caused a significant increase of late complications. In the present analysis, using both univariate and multivariate approaches, neither overall treatment time of radiotherapy nor duration of the split pause appeared as prognostic factors for local control or survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the univariate analysis a treatment interruption of 7 days or more showed a significant impact, but this was lost in the multivariate analysis. Several authors have shown total treatment time to predict treatment outcome and therefore treatment interruptions are not recommended (16,18,22,24,25,27).…”
Section: Discussionmentioning
confidence: 99%